Modelling of Mass Transfer in Osmotic Dehydration of Aonla Slices - Alam, Md. Shafiq; Singh, Amarjit (Journal of Agricultural Engineering, 2008)
The study on osmotic dehydration of aonla slices was carried out in order to remove the moisture prior to the further mechanical drying. Three sugar concentration levels (50degree B, 60degree B and 70degree Brix), three temperature levels of osmotic solution (30degree C, 45degree C and 60degree C) and constant solution to fruit ratio of 6: 1 (V/W) were selected and the observations on water loss and solute gain were taken at an interval of 15, 30, 60, 90, 120, 180 and 240 min. A two-parameter mathematical model developed by Azuara et al. was used for describing the mass transfer in osmotic dehydration of aonla slices. The effect of time on mass transfer kinetics was investigated and the constants of two-parameter model and final equilibrium points for moisture loss as well as solute gain were found. The water loss from and solute gain by the aonla samples increased non-linearly with the duration of osmosis at all sugar concentrations, and both were higher in the initial period of osmosis than the later period. Further, both increased with increasing sugar concentration. The model was able to predict osmosis mass transfer data up to the equilibrium point using data for relatively short period of osmosis.